Modal Sosial Dan Modal Manusia Pada Usaha CV Manado Agro Sentosa - Pantas, Monica; Ngangi, Charles Reijnaldo; Lolowang, Tommy Ferdy (AGRI-SOSIOEKONOMI, 2024)
This study aims to describe the social capital and human capital that exist in the Manado Agro Sentosa CV business. This research was conducted from August to October 2023. The data used were primary data and secondary data. Primary data was collected through field observations and interviews with business owners, employees, suppliers and consumers. Secondary data is obtained through information from within the company, from the internet through google scholar in the form of books, journal articles and theses related to the research topic. The sampling method used purposive sampling method which was taken as many as 6 informants based on appropriate criteria to be used as informants. The results showed that social capital including trust, networks and norms had been built by business owners with various parties, namely employees, suppliers and consumers. Human capital owned by the owner is obtained through education and experience which helps in the process of business activities at CV Manado Agro Sentosa.